Evaluation of a policy intervention to promote the health and wellbeing of workers in small and medium sized enterprises - a cluster randomised controlled trial - Thrive at Work Wellbeing Programme Collaboration (BMC, 2019)
Abstract Background Good employee health and wellbeing is of key importance to employers and the economy. The workplace can serve as a setting for health and wellbeing promotion. Financial incentives may encourage employers to invest in employee health and wellbeing. The aim is to evaluate the effectiveness of health and wellbeing financial incentives offered to small medium enterprises in the West Midlands, UK. Methods A cluster randomised controlled trial was designed to evaluate the effectiveness of a workplace health and wellbeing initiative with or without monetary incentives. We will evaluate the effectiveness of the financial incentive using a mixed methods evaluation approach. Discussion The trial will help establish whether small-medium enterprises will improve their health and wellbeing offer and achieve higher employee awareness and participation in the offer in response to a monetary wellbeing incentive. Trial registration AEARCTR-0003420, registration date: 17.10.2018, retrospectively registered.